Penerapan K3 Dalam Penanganan Pestisida Di Desa Layoa Kecamatan Gantarangkeke Kabupaten Bantaeng - Muh. Rifo Rianto; Anita Anita; Andi Fatmawati (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2020)
Abstract Layoa Village, Gantarangkeke Subdistrict, Bantaeng Regency is one of the main agricultural centers in South Sulawesi, where most of the people have a livelihood as farmers by planting rice, chili peppers, and potatoes. One effort made by farmers in Layoa Village, Gantarangkeke Subdistrict, Bantaeng Regency to increase the productivity of agricultural production is to use pesticides so that crops are not damaged by pests and diseases. From the survey results, it was found that farmers in Layoa Village, Gantarangkeke Subdistrict, Bantaeng Regency have limited knowledge and understanding of the dangers of pesticides and not using work equipment that meets occupational safety and health standards which is a factor causing the risk of health problems due to pesticide exposure. Therefore, the extension team provided a solution in the form of efforts to increase the knowledge and understanding of the farming community in the Village of Layoa about the types of pesticides that are harmful to human health, the impact of pesticides on human health and the application of work safety when using pesticides. The material is delivered through presentation and distribution of farmers' materials, question and answer session or discussion and evaluation. From the community service activities, it can be concluded that the knowledge and understanding of the people of Layoa Village, Gantarangkeke Subdistrict, Bantaeng District increased the benefits of applying work safety in handling pesticides and the dangers of diseases caused by pesticides which are harmful to human health.